Platinum carbonyl clusters stabilized by Sn(ii)-based fragments: syntheses and structures of [Pt6(CO)6(SnCl2)2(SnCl3)4]4−, [Pt9(CO)8(SnCl2)3(SnCl3)2(Cl2SnOCOSnCl2)]4− and [Pt10(CO)14{Cl2Sn(OH)SnCl2}2]2−. Issue 12 (22nd January 2016) - Bortoluzzi, Marco; Ceriotti, Alessandro; Ciabatti, Iacopo; Della Pergola, Roberto; Femoni, Cristina; Carmela Iapalucci, Maria; Storione, Alba; Zacchini, Stefano
Abstract : Low valent Pt carbonyl clusters decorated by Sn(ii ) fragments have been obtained from [Pt15 (CO)30 ] 2− and SnCl2 . Abstract : The reaction of [Pt15 (CO)30 ] 2− with increasing amounts of SnCl2 affords [Pt8 (CO)10 (SnCl2 )4 ] 2− (2 ), [Pt10 (CO)14 {Cl2 Sn(OH)SnCl2 }2 ] 2− (5 ), [Pt6 (CO)6 (SnCl2 )2 (SnCl3 )4 ] 4− (3 ), [Pt9 (CO)8 (SnCl2 )3 (SnCl3 )2 (Cl2 SnOCOSnCl2 )] 4− (4 ) and [Pt5 (CO)5 {Cl2 Sn(OR)SnCl2 }3 ] 3− (R = H, Me, Et, and i Pr) (1-R ).1-R and2 have been previously described, whereas3–5 are herein reported for the first time. The species1–3 are the main products of the reaction under different experimental conditions, whereas4 and5 are by-products of the synthesis of3 and2, respectively. From a structural point of view, the clusters1–5 all show a perfect segregation of the two metals, which are composed of a low valent Pt core decorated on the surface by Sn(ii ) fragments such as SnCl2, [SnCl3 ] −, [Cl2 Sn(OH)SnCl2 ] − and [Cl2 SnOCOSnCl2 ] 2− . These fragments behave as two electron donor ligands via each Sn-atom (and also the C-atom in the case of [Cl2 SnOCOSnCl2 ] 2− ). The [Cl2 SnOCOSnCl2 ] 2− ligand is rather unique and may be viewed as a bis-stannyl-carboxylate, a carbon dioxide μ3 :k 3 - C, O, O ′-CO2 or a carbonite ion [CO2 ] 2− stabilized by coordination to metal atoms. Compounds1–5 have been fully characterised via IR spectroscopy, X-ray crystallography and DFT calculations.